Antiphospholipid syndrome - Pavlović Dragan M.; Pavlović Aleksandra M. (Srpski Arhiv za Celokupno Lekarstvo, 2010)
Antiphospholipid syndrome (APS) is an autoimmune disease with recurrent thromboses and pregnancy complications (90% are female patients) that can be primary and secondary (with concomitant autoimmune disease). Antiphospholipid antibodies are prothrombotic but also act directly with brain tissue. One clinical and one laboratory criterion is necessary for the diagnosis of APS. Positive serological tests have to be confirmed after at least 12 weeks. Clinical picture consists of thromboses in many organs and spontaneous miscarriages, sometimes thrombocytopaenia and haemolytic anaemia, but neurological cases are the most frequent: headaches, stroke, encephalopathy, seizures, visual disturbances, Sneddon syndrome, dementia, vertigo, chorea, balism, transitory global amnesia, psychosis, transversal myelopathy and Guillain-Barre syndrome. About 50% of strokes below 50 years of age are caused by APS. The first line of therapy in stroke is anticoagulation: intravenous heparin or low-weight heparins. In chronic treatment, oral anticoagulation and antiplatelet therapy are used, warfarin and aspirin, mostly for life. In resistant cases, corticosteroids, intravenous immunoglobulins and plasmapheresis are necessary. Prognosis is good in most patients but some are treatment-resistant with recurrent thrombotic events and eventually death.